Bilateral forearm compartment syndrome in a collegiate rower - Thomson, K. B.; Carson, E.; Chhabra, A. B. (Journal of Athletic Training, 2012)
Background: An 18-year old female collegiate rower presented with initial complaints of swelling, tightness and cramping in her left forearm with high intensity rowing, but symptoms resolve within several minutes after practice. The severity of symptoms increased with higher intensity training on the water and on the rowing ergometer. The consistency of the symptoms gradually increased over the next two weeks including slight numbness and tingling in the hand and fingers. Upon examination, point tenderness in both flexor and extensor masses, mild loss of strength compared bilaterally, and slight limitation with wrist flexion and extension motion were noted. Neurological symptoms were not reproducible upon examination. Approximately one month after initial symptoms occurred, the athlete reported having similar symptoms in her right forearm. No previous history of injury to either upper extremity was noted. Differential Diagnosis: Muscle strain, delayed onset muscle soreness, blood clot, compartment syndrome. Treatment: Initial treatment of symptoms included ice and premodulated electrical stimulation, ultrasound, and deep tissue massage (Graston technique). Compression wraps and sleeves would temporary diminish symptoms during activity and partially decrease symptoms after activity. After two weeks of treatment with no dramatic decrease of symptoms, the athlete was referred for evaluation by an orthopedic surgeon. Radiographs and MRI were performed to rule out any bony or soft tissue injury. EMG testing was performed to rule out any neurological injury due to numbness and tingling in the left hand. These tests were also performed on the right arm subsequent to symptoms appearing in the contralateral arm. All tests were normal. Compartment testing was then performed bilaterally. Pre-exercise compartment values were elevated in the following compartments: bilateral superficial volar, right deep volar, right compartment with Wad of Henry (brachioradialis, extensor carpi radialis brevis, and extensor carpi radialis longus). The athlete was then placed on an ergometer and asked to perform a 2,000-meter test at maximal effort. Testing was stopped once peak symptoms were reproduced. Postexercise compartment values were immediately evaluated. Values were elevated in the following compartments: bilateral superficial volar, bilateral deep volar, and right compartment with Wad of Henry. Final diagnosis was bilateral chronic exertional compartment syndrome (CECS). The athlete was referred to a hand surgeon. Since she had not responded to conservative treatment and wanted to continue to row, surgical options were discussed. The athlete decided to have surgery to release multiple volar and dorsal compartments bilaterally. She began a home exercise program consisting of light range of motion and strengthening exercises two weeks post-op while at home for winter break. She was able to start a gradual return to ergometer and rowing activity after six weeks, was back to full activity within 10 weeks, and required occasional treatment for forearm tightness caused by scar tissue and soreness throughout the spring season. Uniqueness: CECS is rarely seen in the upper extremities, especially in athletes. A PubMed search for "chronic exertional compartment syndrome" and "forearm" resulted in only 19 articles, none of which referenced rowing. The lack of previous literature illustrates the uniqueness of such a case in the sport. Also, the athlete`s initial symptoms were unilateral and only became bilateral after approximately a month. Conclusions: While rare, CECS should be considered when evaluating rowers complaining of chronic forearm pain and tightness. Athletes should be referred for testing to confirm the diagnosis prior to surgical intervention. Surgical intervention may be a consideration if all conservative measures have failed. Rowing technique should also be evaluated as a potential cause of increased grip force placed on the handle by the athlete.